Optimisation of solvolysis for recycling carbon fibre reinforced composites - Keith, Matthew J.; Oliveux, Géraldine; Leeke, Gary A. (Unknown, 2016)
Solvolysis processes have been used to degrade the resin of two different varieties of epoxy based carbon fibre reinforced composite (CFRC) materials. A degradation of up to 98% has been achieved when processing material at a temperature of 320 °C using a supercritical solvent mixture of acetone and water. Increasing the processing time from 1 to 2 hours shows an increase in the degradation of only 10% and there does not appear to be any benefit in processing the material beyond this time. Due to the batch conditions used, it is necessary to rinse the fibres with acetone after processing to remove remaining organic residue. Washing the fibres at supercritical batch conditions, however, does not efficiently remove the residue compared to a simple hand washing with acetone. Shredding the sample prior to processing also does not have a significant effect. The process investigated requires 19 MJ.kg-1 of fibres recovered and, since the process has not yet been optimised, shows strong potential for future development especially since it allows for the recovery and reuse of organic resinous products.
Keywords: Composites; carbon fibre; recycling; solvolysis